IMPROVEMENT OF SEEDLING ESTABLISHMENT OF WET SEEDED RICE USING GA3 AND IBA AS SEED TREATMENT - Sri Wahyuni; Uma R. Sinniah; Mohd. Khanif Yusop; Rajan Amarthalingam (Indonesian Journal of Agricultural Science, 2003)
Direct seeding has some advantages compared to transplanting system in rice, however there are some constraints need to be addressed. One  constraint generally faced in the wet seeded rice is poor stand  establishment. The experiment was conducted to improve seedling  establishment by using selected growth regulators. Seeds of four rice  cultivars, i.e. Memberamo, Widas, MR 84, and MR 219 were treated with  GA3 (gibberellic acid-3) of 25, 50, and 100 mg 1-1, and IBA (indole-3  butyric acid) of 10, 20, and 40 mg l-1. Results showed that cultivar  response to GA3 was similar in all parameters observed, however the response of cultivars to IBA was different at the initial stage. In Indonesian cultivars (Memberamo and Widas), shoot length of IBA treated seedlings was comparable to the control, but the IBA treated seedlings of  Malaysian cultivars (MR 84 and MR 219) had slightly shorter shoots   compared to the control. GA3 as seed treatment induced favorable early emergence and shoot growth in the initial stage, but the shoots were  etiolated and resulted in susceptible to lodging even in the vegetative  stage. In comparison, exogenous application of IBA resulted in high number of adventitious roots contributing towards better establishment of seedling with broader and greener leaves. The growth regulator was lost its  effect by 2 or 3 weeks after sowing. All IBA concentrations also did not  show any significant differences on growth parameters or have any detrimental effect on grain yield in all cultivar tested. IBA 10 mg l-1 was  sufficient in providing the required improvement in the rice seedlings.